2013
DOI: 10.1007/s11032-013-9979-9
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, genetic mapping, and signatures of domestication in the carrot (Daucus carota L.) genome, as revealed by Diversity Arrays Technology (DArT) markers

Abstract: Carrot is one of the most economically important vegetables worldwide, but genetic and genomic resources supporting carrot breeding remain limited. We developed a Diversity Arrays Technology (DArT) platform for wild and cultivated carrot and used it to investigate genetic diversity and to develop a saturated genetic linkage map of carrot. We analyzed a set of 900 DArT markers in a collection of plant materials comprising 94 cultivated and 65 wild carrot accessions. The accessions were attributed to three separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 34 publications
8
51
1
Order By: Relevance
“…The 906 DArT markers were also found to be useful in providing a complete picture of genetic diversity in the Miscanthus collection of 180 accessions. Overall, the average PIC (0.22) of the Miscanthus microarray DArT markers was found to be lower than that observed in other plant species where similar markers were developed, such as wheat (0.44) (Raman et al 2010), cassava (0.42) (Xia et al 2005), sorghum (0.41) (Mace et al 2008), and carrot (0.30) (Grzebelus et al 2014), but comparable to that observed in Asplenium fern (0.21) (James et al 2008), Lesquerella (0.21) (Von Mark et al 2013) and sugar beet (0.28) (Simko et al 2012). Around 25.5 % of the DArT markers exhibited a PIC value in the range of 0.40 and 0.50 and these markers might be considered particularly informative.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…The 906 DArT markers were also found to be useful in providing a complete picture of genetic diversity in the Miscanthus collection of 180 accessions. Overall, the average PIC (0.22) of the Miscanthus microarray DArT markers was found to be lower than that observed in other plant species where similar markers were developed, such as wheat (0.44) (Raman et al 2010), cassava (0.42) (Xia et al 2005), sorghum (0.41) (Mace et al 2008), and carrot (0.30) (Grzebelus et al 2014), but comparable to that observed in Asplenium fern (0.21) (James et al 2008), Lesquerella (0.21) (Von Mark et al 2013) and sugar beet (0.28) (Simko et al 2012). Around 25.5 % of the DArT markers exhibited a PIC value in the range of 0.40 and 0.50 and these markers might be considered particularly informative.…”
Section: Discussioncontrasting
confidence: 59%
“…The DArT technology is very suitable for high-throughput work and has been determined to have clear advantages in time and cost aspects of genotyping, in that it allows simultaneously type hundreds or thousands loci in a single array without prior knowledge genome sequence. The DArT technology has been Simko et al 2012;Castillo et al 2013;Grzebelus et al 2014), but no information is available on Miscanthus till date. In the present study, the DArT platform for Miscanthus collection were found both acceptable and provided robust information about the genetic variation in this collection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, DArT has assumed the status of highly reliable, robust and useful markers for analysis of genetic diversity, as well as genetic mapping using linkage or association studies both in a variety of model and non-model crops such as Eucalyptus Restriction digestion, ligation of adapters, end sequencing and sequence analysis Baird et al (2008) Specific-locus amplified fragment sequencing (SLAF-seq) Deep sequencing, Sequence alignment Sun et al (2013) pearl millet (Supriya et al, 2011), carrot (Grzebellus et al, 2014), barley (Lex et al, 2014), sugarcane (Aitken et al, 2014). Subtracted diversity array (SDA; Li et al, 2006) is an advancement over DArT incorporating the benefits of subtractive suppression hybridization (SSH) based microarray, in order to enrich the resulting data with polymorphic genomic DNA sequences.…”
Section: Diversity Arrays Technologymentioning
confidence: 99%